PERSEPSI PETERNAK BEBEK TERHADAP PROGRAM USAHA MIKRO TELUR ASIN ASAP DI DESA SLOROK KECAMATAN DOKO KABUPATEN BLITAR - Alfata, Abdul Hanif; Azizah, Siti (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
Cultivation ability is determined by how farmers perceive their business, if they have a good perception, the management provided will also be better. When the research starts from July 2021 to February 2022, the informant selection technique used is non-probability sampling with a purposive selection of informants logic. Determination of key informants is done by taking informants from 4 Hamlets, the data analysis used is the Miles and Huberman Model. Breeders have a positive perception of the smoked salted egg program, a positive perception evidenced by the components and the perception process. Information taken is smoked salted egg center, smoked salted egg processing, and marketing. Farmers argue that this program can advance the village, farmers cannot retrieve information on organic feed.